2019
DOI: 10.1002/ajoc.201900555
|View full text |Cite
|
Sign up to set email alerts
|

User‐Friendly Copper‐Catalysed Reduction of Azides to Amines

Abstract: Three homoleptic copper(I) complexes have been prepared and applied to the reduction of organic azides. Under optimised conditions, complex [Cu(HPDIDMA)2]BF4 3 (HPDIDMA=2,6‐bis[N‐(4‐dimethylaminophenyl)carbaldimino]pyridine) could reduce a range of electron‐poor azides in a mixture of DMSO and water without the need of an additional H‐source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Given the fact that the azide reduction to an amine proceeds together with the deposition of Cu over the course of the reaction, it removes one equivalent of available azide from the mixture and alters the Cu-azide ratio. In addition, the Cu-mediated amination proceeds via reactive Cu-nitrenes, , and the mass recovery was nearly identical when the catalyst was prepared with and without the presence of BrPhAc . The completion of the amination, to 1,4-acetylaniline, was confirmed by 1 H NMR spectroscopy in the current experiment with BrPhAc , which confirms that the reaction is not inhibited by the presence of CB.…”
Section: Resultsmentioning
confidence: 87%
“…Given the fact that the azide reduction to an amine proceeds together with the deposition of Cu over the course of the reaction, it removes one equivalent of available azide from the mixture and alters the Cu-azide ratio. In addition, the Cu-mediated amination proceeds via reactive Cu-nitrenes, , and the mass recovery was nearly identical when the catalyst was prepared with and without the presence of BrPhAc . The completion of the amination, to 1,4-acetylaniline, was confirmed by 1 H NMR spectroscopy in the current experiment with BrPhAc , which confirms that the reaction is not inhibited by the presence of CB.…”
Section: Resultsmentioning
confidence: 87%
“…The most prominent peaks in the high-resolution mass spectrum (Supporting Information, page S10) are assigned to the structures T1−T3 shown in Scheme 1. It has been previously suggested that similar copper-mediated in situ amination reactions proceed via highly reactive nitrene intermediates, 24,25,36 which may be copper-stabilized. 36 We have proposed a similar pathway for the amination in EtOH/ water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Based on these data, we propose amine formation proceeds via nitrene intermediates, in agreement with earlier reports of comparable systems (Scheme 2a). 24,25,36 Initially, aromatic halogen−azide exchange occurs, followed by elimination of N 2 generating a, possibly Cu-stabilized, nitrene. It reacts in a stepwise manner with available hydrogens to afford the amine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent catalytic reduction of the nitro group yields the desired amino group. Reducing an azide group at the C‐7 position [42–44] can also produce amine moieties. Azides are essential intermediates in medicinal chemistry, enabling the synthesis of heterocycles such as triazoles and tetrazoles, allowing quinolone‐triazole or tetrazole hybrids to be generated [45–48] …”
Section: Resultsmentioning
confidence: 99%